Registration of Positron Emission Tomography (PET) Image and Functional Near Infrared Spectroscopy (NIRS) Data - Fairuz, Mohd Nasir; Asuka, Kikuchi; Shoichi, Watanuki (2019)
Functional near infrared spectroscopy (NIRS) is the optical imaging that measures changes of blood hemodynamic while positron emission tomography (PET) measure physiological condition of the interest area. NIRS has high temporal resolution while PET image has better spatial resolution compared, however, NIRS measures hemodynamic changes in the cortex region but not in deeper brain structures. Therefore, this study is aimed to register the both image; the NIRS data on the PET image. The registration of NIRS on PET image was done on eleven subjects which undergoes NIRS and PET scan separately. To register the NIRS probe on the PET image, we did a transformation of NIRS probe coordinate to the PET coordinate based on Polaris marker position attached to the NIRS cap. The coordinate of these markers is obtained using the optical tracking system, Polaris. The resulting image forms PET and NIRS were visually aligned as well as the coordinate of the marker obtained during the PET acquisition. The probe was registered on the PET image using the in-house software. The registration done in this study is considered successful as we can view the NIRS activation area on PET image.